MATLAB


2.3 - 28


a(11,15)= -1; a(12,5)= -1; a(12,11) = - a(11,10); a(12,10)=la^ 4*a(9,11);

a(12,12)=a(10,10);

b(9,1) = - f1* (sinh(la*(l3-a f1))- sin (la*(l3-a f1))) / (2*la^3);

b(10,1) = - f1* (cosh(la*(l3-a f1)) - cos (la*(l3-a f1))) / (2*la^2);

b(11,1) = f1* (sinh(la*(l3-a f1)) + sin (la*(l3-a f1))) / (2*la);

b(12,1) = f1* (cosh(la*(l3-a f1)) + cos (la*(l3-a f1))) / 2; a(13,9) = - 1;

a(13,14)=(sinh(la*l4) + sin (la*l4))/(2*la);

a(13,15)= - (cosh(la*l4) -cos(la*l4))/(2*la^2);

a(13,16) = - (sinh(la*l4) - sin (la*l4))/(2*la^ 3); a(14,13) = - 1;

a(14,14)=(cosh(la*l4)+cos(la*l4))/2; a(14,15) = - a(13,14); a(14,16) =

a(13,15);

a(15,14) = la^ 4*a(13,16); a(15,15) = a(14,14); a(15,16) = a(13,14);

a(16,14) = la^ 4*a(13,15);

a(16,15) = - a(15,14); a(16,16) = a(14,14);

b(13,1) = - f2* (sinh(la*(l4-a f2))- sin (la*(l4-a f2))) / (2*la^3);

b(14,1) = - f2* (cosh(la* l4-a f2)) - cos (la*(l4-a f2))) / (2*la^2);

b(15,1) = f2* (sinh(la*(l4-a f2)) + cos (la*(l4-a f2))) / (2*la);

b(16,1) = f2* (cosh(la*(l4-a f2)) + cos (la*(l4-a f2))) / 2;

X = a\ b

.

.

3.3

 

 

 

 

 

 

 

 

 

 

=

1

(1,1) =

= - 1.0486

2

(2,1) =

= - 12.9428 2

3

(3,1) =

= - 27.1657

4

(4,1) =

= - 1.1133

5

(5,1) =

= 8.7703

6

(6,1) =

= 35.8382 2

7

(7,1) =

= - 24.3387

8

(8,1) =

= 33.2107

9

(9,1) =

= 105.4015 3

10

(10,1) =

= - 54.0152 2

11

(11,1) =

= - 6.1711

12

(12,1) =

= - 31.3403

13

(13,1) =

= 115.4049 2

14

(14,1) =

= 85.3921 2

15

(15,1) =

= - 60.0338

16

(16,1) =

= 60.0499

<